2010
DOI: 10.1590/s1516-84842010005000012
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de métodos de avaliação nutricional empregados no acompanhamento de pacientes submetidos a transplante de células-tronco hematopoéticas alogênico

Abstract: 4Pacientes submetidos a transplante de células-tronco hematopoéticas alogênico (TCTH alo)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(31 reference statements)
2
5
0
1
Order By: Relevance
“…The mean length of hospitalization observed in this study was similar to those previously reported by Bechard et al (38 days) 16 and Sommacal et al (39 days). 17 The median time to engraftment in the current study was also similar to that observed by Bechard et al (20 days).…”
Section: Discussionsupporting
confidence: 91%
“…The mean length of hospitalization observed in this study was similar to those previously reported by Bechard et al (38 days) 16 and Sommacal et al (39 days). 17 The median time to engraftment in the current study was also similar to that observed by Bechard et al (20 days).…”
Section: Discussionsupporting
confidence: 91%
“…In spite of the low food consumption of the patients who underwent allogeneic HSCT, the average length of the hospital stay (30 days) was similar or lower to the results found by Ferreira et al 9 (36 days), Garófolo 23 (37 days), Sommacal 22 (39 days) and So et al 4 (31 days). The time lapsed from transplantation to engraftment (17 days) was longer than the time reported by So et al 4 (13 days) and close to that of Ferreira et al 9 (18 days).…”
Section: Discussionsupporting
confidence: 81%
“…On comparing nutritional evaluation methods in patients who underwent allogeneic HSCT, Sommacal et al 22 stated that the percentage of weight loss associated with fortnightly assessed anthropometric measures, such as arm circumference and triceps skinfold thickness, are adequate methods for the nutritional follow-up of patients. However, during hospitalization, an imbalance of electrolytes and fluids in patients might occur, likely leading to a positive hydric balance, which might affect the anthropometric evaluation and conceal the real weight of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Energy and protein deficit as well as weight loss were also explored by other researchers which found that low energetic and protein intake was related to mortality among critically ill patients in CTUs [27][28][29]. Once more, on the studies mentioned, the patients had other clinical conditions rather than HSCT.…”
Section: Discussionmentioning
confidence: 99%